Investigation of thermo-elastic buckling of variable stiffness laminated composite shells using finite element approach based on higher-order theory. (1st March 2019) - Aditya Narayan, D.; Ganapathi, M.; Pradyumna, B.; Haboussi, M.
Highlights: Numerical investigation of thermo-elastic buckling of variable stiffness laminated composite shell panels. Finite element based on a higher-order theory developed for thermal buckling. Laminates with curvilinear fibers resulting in spatially variable stiffness composite shells are treated. A comprehensive study is made considering many design parameters and thermal fields. New results for the thermal elastic stability of such composite panels are provided. Abstract: Here, the thermo-elastic buckling characteristics of variable stiffness composite shells, viz., cylindrical and spherical shell panels, subjected to uniform/non-uniform thermal fields are investigated based on finite element approach introducing higher-order theory accounting through thickness effect. The variable stiffness in the composite laminate is spatially created introducing curvilinear fibers that continuously changes the fiber orientation within the lamina. The critical buckling temperature is evaluated solving the governing equations developed through the principle of minimization of total potential energy by adopting the eigenvalue approach. To select the appropriate structural model, the thermal buckling of such curved panels subjected to thermal fields are initially examined using different structural theories. To predict the buckling temperature, the thermal stress resultants are firstly evaluated using the displacement fields of pre-buckling of the laminated shells under the assumed temperature. The formulation is tested against considering problems for which analytical/numerical solutions available in the literature. A comprehensive study based on various design factors such as curvilinear fiber angular variation, lay-up, length-to- and radius-to-thickness ratios, and boundary conditions on the thermoelastic stability of laminated composite shell panels is made.